Social Repercussions of Pandemics - Barrett, Philip; Chen, Sophia (Washington, D.C. : International Monetary Fund, 2021)
Epidemics may have social scarring effects, increasing the likelihood of social unrest. They may also have mitigating effect, suppressing unrest by dissuading social activities. Using a new monthly panel on social unrest in 130 countries, we find a positive cross-sectional relationship between social unrest and epidemics. But the relationship reverses in the short run, implying that the mitigating effect dominates in the short run. Recent trends in social unrest immediately before and after the COVID-19 outbreak are consistent with this historic evidence. It is reasonable to expect that, as the pandemic fades, unrest may reemerge in locations where it previously existed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet